2023
DOI: 10.2196/45301
|View full text |Cite
|
Sign up to set email alerts
|

Digital Adherence Technologies and Mobile Money Incentives for Management of Tuberculosis Medication Among People Living With Tuberculosis: Mixed Methods Formative Study

Abstract: Background Although there is an increasing use of digital adherence technologies (DATs), such as real-time monitors and SMS reminders in tuberculosis medication adherence, suboptimal patient engagement with various DATs has been reported. Additionally, financial constraints can limit DAT’s utility. The perceived usefulness and the design mechanisms of DATs linked to mobile money financial incentives for tuberculosis medication management remain unclear. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This is supported by another study that reported financial constraints as a notable limitation and proposed a potential role for financial incentives. 34 …”
Section: Discussionmentioning
confidence: 99%
“…This is supported by another study that reported financial constraints as a notable limitation and proposed a potential role for financial incentives. 34 …”
Section: Discussionmentioning
confidence: 99%
“…A study done in South Africa reported that the acceptability of DAT was highly associated with its ease of use among patients [ 12 ]. The real-time medication monitoring reports and feedback on adherence helped patients understand their health conditions and led to improved patient and health care provider relationships [ 12 , 24 , 25 ]. In addition, it led to improved care practice and behavior change among TB care providers.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the My Mobile Wallet intervention are described elsewhere [ 13 ]. Briefly, as shown in Figure 2 , the intervention is composed of the following 3 components: a real-time medication monitor (Wisepill evriMED1000) to monitor medication adherence by sending signals when opened (the monitor records a date-and-time stamp as a proxy for taking medication, and it has an option to set an alarm sound to remind patients to take their medication); SMS text message reminders sent to users’ mobile phones to remind them to take their medication as prescribed (reminders are sent daily for 2 months, after which they are triggered as needed by missed or delayed doses); and the WiseCash app, which uses a tailored mobile money platform for sending financial incentives for transport to the clinic and motivating medication adherence.…”
Section: Methodsmentioning
confidence: 99%
“…The use of mobile money technology (money sent, received, or saved on mobile phones) is a promising tool for delivering health-related cash transfers; for instance, mobile money enabled pregnant women to save for maternal health care in Kenya [ 11 ], while a progressive incentive scheme to reward private physicians and community health care workers enhanced identification and referral of suspected tuberculosis cases and treatment tracking in Pakistan [ 12 ]. The use of mobile money transfers to incentivize patients living with tuberculosis to take their drugs may potentially improve their adherence to medication [ 13 ]. However, the use of mobile money services in the context of health care is still in its infancy, and the limited research in this area reports mixed results [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation